2008
DOI: 10.1177/0956247808089153
|View full text |Cite
|
Sign up to set email alerts
|

Microfinance for community development, poverty alleviation and natural resource management in peri-urban Hubli-Dharwad, India

Abstract: This paper reports on the fi ndings of a study of a microfi nance and community mobilization initiative in six villages in the peri-urban zone of HubliDharwad in Karnataka state, southern India, where a number of self-help groups established by two NGOs were studied over a three-year period (2001)(2002)(2003)(2004). Despite deliberate targeting of the poor and very poor sectors, their representation in the self-help groups was found to be no different from their proportions in the populations of the villages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…It can also increase overall wealth, since, as Brook, Hillyer, and Bhuvaneshwari (2008) point out, the poor and very poor are more actively involved in microfinance than members of other wealth classes. Ecological resources, whether aquatic or terrestrial, have contributed to human welfare and development.…”
Section: Links Between Microfinance Poverty and The Environmentmentioning
confidence: 99%
“…It can also increase overall wealth, since, as Brook, Hillyer, and Bhuvaneshwari (2008) point out, the poor and very poor are more actively involved in microfinance than members of other wealth classes. Ecological resources, whether aquatic or terrestrial, have contributed to human welfare and development.…”
Section: Links Between Microfinance Poverty and The Environmentmentioning
confidence: 99%
“…Most impact assessment studies (while comparing microfinance clients with non‐clients) considered homogeneity in the endogenous factors of self‐selection (Armendariz and Morduch, 2007; Coleman, 1999; Kando, ; Panda, ). Indian studies have explained the homogenous attributes of microfinance beneficiaries when members are self‐selected (Athavale et al ., ; Brook et al ., ; Panda and Atibudhi, ). The National Bank of Agriculture and Rural Development expresses SHG members as homogenous in their socioeconomic background .…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable evidence elucidating microfinance impacts on microenterprises. Microfinance interventions had led to self‐employment and microenterprise development in Bangladesh (Chowdhury, , ; Khandker et al ., ), the Philippines (Hossain and Diaz, ), and India (Brook et al ., ; NABARD, ; Panda, ). Studies observed that microfinance programs have generated good business sense for poor women across the world (Eversole, ; Hickson, ; Rutherford, ).…”
mentioning
confidence: 99%
“…Terkait dengan strategi pemberdayaan ekonomi komunitas miskin sebagai upaya penanggulangan kemiskinan telah dikaji Wulan, Ati, & Widodo (2019) terkait implementasi program Kelompok Usaha Bersama (KUBE) di salah satu wilayah perkotaan di Jawa Timur menyebutkan bahwa fasilitasi bantuan permodalan berperan penting dalam menumbuhkan usaha produktif bagi anggota kelompok. Sedangkan Brook, Hillyer, & Bhuvaneshwari (2008) mengkaji komunitas miskin di wilayah India merupakan penerima manfaat program kredit mikro yang diinisiasi oleh organisasi non-pemerintah. Hasil kajiannya mendeskripsikan bahwa program dapat berhasil meningkatkan level kesejahteraan keluarganya sebesar 77% karena didorong oleh adanya upaya mobilisasi perubahan perilaku dan akses penerima manfaat sehingga mereka menjadi lebih mandiri.…”
Section: Pendahuluanunclassified